Formalization of correlational studies of water problems - Javier, Carreon Guillen; Cruz, García Lirios; Celia, Yaneth Quiroz Campas; Elías, Alexander Vallejo Montoya; Francisco, Espinoza Morales; Victor, Hugo Meriño Córdoba; Carmen, Ysabel Martínez de Meriño; Luiz, Vicente Ovalles Toledo; Clara, Judith Brito Carrillo; Arger, Verstapp Bund (Journal of Model Based Research, 2023)
A methodological note proposes formal structures for correlational studies of water problems. It emphasizes variable definition, confounding control, and reproducibility.
Keywords: Conformity; dependency; conflict and hydrological innovation